2011
DOI: 10.1186/bcr2857
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the epidermal growth factor receptor (EGFR) gene in triple negative breast cancer: possible implications for targeted therapy

Abstract: IntroductionTriple negative breast cancer is associated with poorer prognosis and unresponsiveness to endocrine and anti-HER2 directed agents. Despite emerging data supporting the use of polyADP-ribose polymerase (PARP) inhibitors, complete and durable responses are rare and exploration of additional targeted therapies is needed. Epidermal growth factor receptor (EGFR) is expressed in triple negative breast cancer and several clinical trials are testing the role of anti-EGFR directed therapy. However, the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 46 publications
6
110
0
1
Order By: Relevance
“…Of the four cases with EGFR mutation, three carried a missense mutation of exon 21 (L858R), one of which with a coexisting 34 so the presence of L858R and G719A mutations in this study population suggests gefitinib or erotinib therapy may be beneficial in these selected triplenegative breast cancer patients. In our study, there was disagreement between EGFR immunostaining and the presence of EGFR mutation, similar to the report of Teng and colleagues, 16 suggesting that positivity in EGFR IHC cannot predict EGFR mutation in triple-negative breast cancer. In this study, high EGFR copy number was significantly associated with poor disease-free survival and acted as an independent poor prognostic factor.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Of the four cases with EGFR mutation, three carried a missense mutation of exon 21 (L858R), one of which with a coexisting 34 so the presence of L858R and G719A mutations in this study population suggests gefitinib or erotinib therapy may be beneficial in these selected triplenegative breast cancer patients. In our study, there was disagreement between EGFR immunostaining and the presence of EGFR mutation, similar to the report of Teng and colleagues, 16 suggesting that positivity in EGFR IHC cannot predict EGFR mutation in triple-negative breast cancer. In this study, high EGFR copy number was significantly associated with poor disease-free survival and acted as an independent poor prognostic factor.…”
Section: Discussionsupporting
confidence: 87%
“…11,17,19,25,26 However, Teng et al reported the presence of EGFR mutation, specifically exon 19 deletions and exon 21 missense (L858R) mutations, in 11% (8/70) of triple-negative breast cancer samples from predominantly Chinese patients. 16 In this study, EGFR mutation was found in 3% (4/151) of triplenegative breast cancer samples from Korean patients. As suggested by Lamy and Jacot, 33 wide variations in the rate of EGFR mutation in different populations may reflect geographic or ethnic differences in the presence of EGFR mutation.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations